p75 Neurotrophin Receptor-Mediated Signaling Promotes Human Hair Follicle Regression (Catagen) - Peters, Eva M.J. (American Society for Investigative Pathology, 2006)
Nerve growth factor (NGF) and its apoptosis-promoting low-affinity receptor (p75NTR) regulate murine hair cycling. However, it is unknown whether human hair growth is also controlled through p75NTR, its high-affinity ligand pro-NGF, and/or the growth-promoting high-affinity NGF receptor tyrosine kinase A (TrkA). In microdissected human scalp anagen hair bulbs, mRNA for NGF, pro-NGF, p75NTR, and TrkA was transcribed. Immunohistomorphometry and in situ hybridization detected strong NGF and pro-NGF expression in terminally differentiating inner root sheath keratinocytes, whereas TrkA was co-expressed with p75NTR in basal and suprabasal outer root sheath keratinocytes. During spontaneous catagen development of organ-cultured human anagen hair follicles, p75NTR mRNA levels rose, and p75NTR and pro-NGF immunoreactivity increased dramatically in involuting compartments primarily devoid of TrkA expression. Here, TUNEL(+) apoptotic cells showed prominent p75NTR expression. Joint pro-NGF/NGF administration inhibited hair shaft elongation and accelerated catagen development in culture, which was antagonized by co-administration of p75NTR-blocking antibodies. In addition, mRNA and protein expression of transforming growth factor-β2 increased early during spontaneous catagen development, and its neutralization blocked pro-NGF/NGF-dependent hair growth inhibition. Our findings suggest that pro-NGF/NGF interacts with transforming growth factor-β2 and p75NTR to terminate anagen in human hair follicles, implying that p75NTR blockade may alleviate hair growth disorders characterized by excessive catagen development.